On the Efficiency of Stock-Based Compensation - Paul, Jonathan M. (Review of Financial Studies, 1992)
[When the market can observe the profitability of all projects with equal precision, then with stock compensation (i) the weight on any given project in managerial compensation is independent of the marginal productivity of effort in the project; (ii) the projects that are the noisiest indicators of managerial effort receive the most weight in compensation; and (iii) investors have the greatest incentive to collect information about projects that are the noisiest indicators of managerial effort.]